Voz e expressividade de professores universitários - Nayara Ribeiro Gomes (2018)
Introduction: The human communication is straightly connected to the form of transmission and compartilhamento of ideas through the voice, the language and non-verbal elements. In teaching, voice is a relevant factor for acting in the classroom, an efficient resource to transmit knowledge and get the attention of the student. Voice problems in teachers are usually related to complaints of vocal fatigue and wear caused by high demand and intense work rhythm that reflect the frequency and under what conditions the teacher uses the voice. Expressivity in communication points to the use of vocal resources used in communicative performance, ensuring that the message is transmitted effectively. The communicator, in the case of the teacher, should develop characteristics of empathy and interaction appropriate to the professional context, aiming at the process of knowledge construction of his students. Aim: investigate the vocal symptoms reported by university professors and check the association with vocal resources and aspects of the work environment. Methodology: It is an observational, analytical, cross-sectional study. The teachers were members of the Federal University of Minas Gerais (UFMG) from 77 different courses and excluded those who were away from work and worked outside the classroom during data collection and the professors graduated in Speech-Language Pathology. The sample calculation was performed considering the prevalence of the event of at least 20%. The sample margin of error is 5% and the level of significance is 95%. The research instrument consisted of 55 questions, which were organized based on the clinical experience of researchers and other protocols that exist in the literature on voice disorder and applied virtually. After the questionnaire was applied, the data were scanned and analyzed using the 14 Excel, STATA (Stata Corporation, College Station) version 12.0. The descriptive analyzes were carried out by means of the absolute and relative frequency distribution of the categorical variables and the numerical synthesis of the continuous variables. To verify the desired associations were performed by logistic regression. The variables with a significance level of 20% in the univariate analysis were considered fit to enter the multivariate model. The magnitude of association was verified by the Odds Ratio and significance level of 5%. Results: 334 teachers, mostly female (n=201), with a mean age of 46 years (SD±10.2) participated in the study. The results showed that the mean number of vocal symptoms was 3.1 (SD±2.75), the most cited being: dry throat (n = 186) and the least cited: difficulty swallowing (n=20). Female teachers were more likely to report five or more symptoms than men. Regarding the association with the investigated variables, we verified that the chance of presenting five or more vocal symptoms increases when the teachers report environment noise as unsatisfactory with speech speed as fast, pitch sharp and loud loudness. Conclusion: Female college professors who perceive ambient noise as unsatisfactory, who speak fast, with sharp pitch and loud loudness exhibit a greater number of vocal symptoms. The results found reinforce the importance of phonoaudiological work with teachers, regarding health promotion and prevention measures to raise awareness about the risk factors for voice.